Análise técnico-econômica e ambiental de biorrefinarias de macroalgas - Kanematsu, Simon (Universidade Federal de São Carlos, 2026)
The development of macroalgae-based biorefineries has emerged as a promising pathway for the sustainable production of biofuels and high-value bioproducts. This thesis evaluates, independently, two industrial-scale routes: cellulose nanocrystals (CNC) production from Sargassum sp. and ethanol production from Kappaphycus alvarezii. The processes were modeled based on the scale-up of experimental data and literature sources, enabling the establishment of mass and energy balances, equipment sizing, and estimation of capital (CAPEX) and operating (OPEX) costs. Economic feasibility was assessed through the Minimum Selling Price (MSP), Net Present Value (NPV), and Internal Rate of Return (IRR), complemented by sensitivity and uncertainty analyses using Monte Carlo simulation, while environmental performance was evaluated following ISO 14040/14044 standards. For CNC production from Sargassum sp., four scenarios were assessed: S1) sap, alginic acid, protein, and CNC; S2) sap, alginic acid, and CNC; S3) sap and CNC; and S4) CNC only. CAPEX ranged from approximately US$113.72 to 141.29 million, while the MSP values were US$14,805.67/ton (S1), US$11,098.54/ton (S2), US$3,521.02/ton (S3), and US$8,546.04/ton (S4). Scenarios with higher product diversification exhibited increased CAPEX without proportional reductions in MSP. The most favorable configuration (S3), focused on CNC and sap production, showed the lowest MSP and best environmental performance. Sensitivity analysis indicated that hydrolysis efficiency, minimum attractive rate of return, and CAPEX are the most critical variables affecting MSP. Uncertainty analysis (95% confidence interval) showed MSP ranges of US$7,694.07-22,102.52/ton (S1), US$5,405.69-16,936.40/ton (S2), US$1,915.80–5,105.39/ton (S3), and US$6,199.59–10,695.37/ton (S4). From an environmental perspective, Life Cycle Assessment (LCA) indicated negative eutrophication potential (EP) values ranging from -0.144 to -0.05 kg PO₄³⁻ eq/kg CNC, associated with nutrient uptake during cultivation, and global warming potential (GWP) values between 1.52 and 10.53 kg CO₂ eq/kg CNC. Independently, ethanol production from Kappaphycus alvarezii was evaluated. The integrated process (including sap, yeast, and carbon credits-CBIOs) presented a CAPEX of US$148 million, IRR of 57.77%, and NPV of US$1,028.69 million. However, ethanol production as a standalone product resulted in a negative NPV (US$-2,003.07 million) and IRR below the minimum attractive rate of return, indicating economic infeasibility. Sensitivity analysis showed strong dependence on sap selling price and biomass throughput, while Monte Carlo simulation indicated a 90.64% probability of positive NPV under integrated conditions. In contrast, LCA results showed highly favorable environmental performance, with negative GWP (-0.6 kg CO₂ eq/kg) and EP (-0.14 kg PO₄³⁻ eq/kg). Overall, macroalgae biorefineries demonstrate strong environmental performance; however, their economic viability is highly dependent on product portfolio and process integration. High-value products such as CNCs improve feasibility, whereas ethanol production requires coproduct valorization, indicating that the main barrier to industrial implementation is economic rather than technical or environmental.
Techno-economic and environmental assesment of a macroalgae biorefinery
Keywords: Biorrefinaria de macroalgas; Análise técnico-econômica; Avaliação do ciclo de vida; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 13. Ação contra a Mudança Global do Clima